2021
DOI: 10.3390/molecules26206154
|View full text |Cite
|
Sign up to set email alerts
|

Orientin Improves Substrate Utilization and the Expression of Major Genes Involved in Insulin Signaling and Energy Regulation in Cultured Insulin-Resistant Liver Cells

Abstract: Our group has progressively reported on the impact of bioactive compounds found in rooibos (Aspalathus linearis) and their capacity to modulate glucose homeostasis to improve metabolic function in experimental models of type 2 diabetes. In the current study, we investigated how the dietary flavone, orientin, modulates the essential genes involved in energy regulation to enhance substrate metabolism. We used a well-established hepatic insulin resistance model of exposing C3A liver cells to a high concentration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 28 publications
(53 reference statements)
0
4
0
Order By: Relevance
“…Sithandiwe et al. 41 found that orientin (10 μM) treatment of insulin-resistant liver cells can combat dyslipidemia or IR. This may be related to orientin improving gene expression of GLUT2, insulin signal transduction (IRS1 and PI3k), and energy regulation (AMPK and Cpt1).…”
Section: Flavonoids: Classification and Biological Propertiesmentioning
confidence: 99%
“…Sithandiwe et al. 41 found that orientin (10 μM) treatment of insulin-resistant liver cells can combat dyslipidemia or IR. This may be related to orientin improving gene expression of GLUT2, insulin signal transduction (IRS1 and PI3k), and energy regulation (AMPK and Cpt1).…”
Section: Flavonoids: Classification and Biological Propertiesmentioning
confidence: 99%
“…When phosphorylated (p‐AMPK‐α), this protein improves the use of glucose (Rena et al., 2013 ), contributing to the reduction of hyperglycemia. In in vitro models, Orientin demonstrated the ability to increase glucose uptake and effectively modulate the expression of genes that encode glucose transport (GLUT2 and GLUT4) (Choi et al., 2020 ; Mazibuko‐Mbeje et al., 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…Another possible mechanism of action of Elo in cardiac dysfunction associated with diabetes is through the modulation of genes that encode insulin signaling. Elo compounds (Orientin and Vitexin) capable of activating insulin receptor substrate‐1 (IRS‐1), in addition to increasing glucose uptake, play an important role in the activation of phosphatidylinositide‐dependent kinase‐3 (PI‐3K) by increasing the phosphorylation of IR, IRS‐1, and IRS‐2 (Choi et al., 2020 ; Ganesan et al., 2020 ; Inamdar et al., 2019 ; Mazibuko‐Mbeje et al., 2021 ). PI‐3K controls the signaling cascade that regulates mitochondrial function, cardiac energy metabolism, and the renin–angiotensin system (Guo & Guo, 2017 ).…”
Section: Discussionmentioning
confidence: 99%
“…Mangiferin is a xanthone present in significant levels in higher plants and possesses a variety of pharmacological actions, including anticancer, antidiabetic, antioxidative, immunomodulatory, hepatoprotective, analgesic, and neuroprotective effects [ 69 , 70 ]. Orientin is a water-soluble flavonoid C-glycoside with antioxidant, antiaging, antiviral, antibacterial, anti-inflammation, vasodilatation and cardioprotective, antiadipogenesis, antinociceptive, radiation-protective, neuroprotective, and antidepressant-like effects [ 71 , 72 , 73 , 74 ]. CB2R was also reported to be involved in the regulation of inflammation, anti-cancer, anti-fibrotic, and nerve system disease [ 10 , 13 ].…”
Section: Discussionmentioning
confidence: 99%